A Multimodal Discourse Analysis on Female Representations in Film Posters - Navarro, Ana Louella N; Adriano, Teresita Q. (CV. Tripe Konsultan, 2024)
This study aims to identify the multimodal features used in film posters of Filipino movies produced between 2010 and 2023 that are currently found on Netflix. It aims to highlight the various stereotypes of women depicted through various multimodal modes using Multimodal Discourse Analysis and anchored on Visual Grammar by Kress and Van Leeuwen and Systemic Functional Linguistics by Halliday. Moreover, through this study, the researcher examined how these representations affected female viewers’ construction of their feminine images and their overall impression on the film posters. There were 40 film posters analyzed and 11 female participants interviewed. The results revealed that the interactional (gaze, size of frame, and perspective), compositional meanings (salience and informational value) of the film posters were tools to display different female representations. Also, the representational meanings made up by vectors and different structures and process underscored different female representations. These representations were also observed in the themes that were developed from the responses of the participants, which include: women’s stereotypical image portrayal, progressive female characters, stereotype subversion, and objectification. Finally, the participants also had similar opinions regarding the influence that film posters have on them when choosing which movies to watch, and the most prominent visual elements that attract the viewers.